EVALUASI UTILITAS KAWASAN DISTRIK MERAUKE SISTEM JARINGAN PERSAMPAHAN KOTA - Biatma Syanjayanta; Hilarius Candra Syanjayakusuma (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2019)
Regional utilities are one of the infrastructures in a city that can support smoothness and comfort in various fields,as well as to fulfill basic human needs in the social and economic sphere. With the existence of utilities, humans can carryout economic activities, transportation, and other activities well. Garbage utility network and services in the city of Merauke,have not yet taken place optimally. With the unavailability of adequate waste facilities, coupled with a low public awarenessabout cleanliness, this will result in uncomfortable conditions in the urban area. In addition, it can also cause negativeimpacts on the region, for example, it can lead to flooding and disease. The utility planning area of the garbage networksystem in the city of Merauke aims to provide a waste network planning design in the city of Merauke, in order to improvethe condition and life quality as well as the provision of waste management facilities. The results of the data analysis thatthe authors did, it is still necessary to plan the addition of facilities for waste system, so that the conditions of the city areaare healthy and comfortable. The results of this paper Merauke city map of solid waste system plan, which is an input to thelocal government of Merauke district.